In vitro and in vivo antibacterial activity of a lysine-rich scorpion peptide derivative. (15th April 2022) - Yuan, Yaping; Li, Shasha; Zhao, Zhuoran; Deng, Bo; Li, Ziyi; Jing, Xiaoyuan; Zhang, Wenlu; Li, Zhongjie
Abstract: Antimicrobial peptides are widely acknowledged as an alternative class of antimicrobial agents. In this study, a lysine-rich scorpion peptide derivative Pacavin-5K was designed, which showed an improved antibacterial spectrum, significantly higher antibacterial activity, and lower toxicity compared to the native peptide. It also showed an improved thermal and serum stability. Notably, Pacavin-5K significantly decreased the bacterial counts in the wounded region in the mouse cutaneous infection model caused by Staphylococcus aureus and Pseudomonas aeruginosa . Moreover, Pacavin-5K did not induce bacterial resistance associated with its antibacterial mechanism disrupting the membrane. Furthermore, Pacavin-5K could kill the S. aureus cells at the biofilm state. Overall, Pacavin-5K could be a potential alternative antibacterial agent against skin infection caused by S. aureus and P. aeruginosa . Graphical abstract: Image 1 Highlights: Pacavin-5K showed excellent antibacterial activity in vitro and in vivo. Pacavin-5K showed excellent thermal and serum stability. Pacavin-5K killed bacterial cells mainly by disrupting the membrane. Pacavin-5K did not induce bacterial resistance. Pacavin-5K could be a potent anti-infective agent against skin infection.